1999
DOI: 10.1006/dbio.1999.9255
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of a Src-Related Tyrosine Kinase inXenopusEgg Activation

Abstract: Recently, we have purified a Src-related tyrosine kinase, named Xenopus tyrosine kinase (Xyk), from oocytes of Xenopus laevis and found that the enzyme is activated within 1 min following fertilization [Sato et al. (1996) J. Biol. Chem. 271, 13250-13257]. A concomitant translocation of a part of the activated enzyme from the membrane fraction to the cytosolic fraction was also observed. In the present study, we show that parthenogenetic egg activation by a synthetic RGDS peptide [Y. Iwao and T. Fujimura, T. (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 56 publications
6
82
0
Order By: Relevance
“…In Xenopus fertilization induces the activation of Src-related protein tyrosine kinases (PTK), which induces PLCg activation through an unknown mechanism (Sato et al, 1999(Sato et al, , 2000Tokmakov et al, 2002). However, PLCg activation in Xenopus does not involve SH2-domain dependent recognition of phospho-tyrosine residues (Runft et al, 1999), in contrast to starfish for example (Carroll et al, 1997).…”
Section: Ca 2r -Dependent Plc Activationmentioning
confidence: 99%
“…In Xenopus fertilization induces the activation of Src-related protein tyrosine kinases (PTK), which induces PLCg activation through an unknown mechanism (Sato et al, 1999(Sato et al, , 2000Tokmakov et al, 2002). However, PLCg activation in Xenopus does not involve SH2-domain dependent recognition of phospho-tyrosine residues (Runft et al, 1999), in contrast to starfish for example (Carroll et al, 1997).…”
Section: Ca 2r -Dependent Plc Activationmentioning
confidence: 99%
“…Activation of SFKs occurs soon after fertilization in sea urchin, zebrafish and Xenopus eggs (Kinsey, 1996;Sato et al, 1999;Abassi et al, 2000;Wu and Kinsey, 2000), and recent studies have suggested that activation of SFK(s) is required for sperm-induced [Ca 2+ ] i release in sea urchin, starfish, ascidian, and Xenopus eggs (Giusti et al, 1999Abassi et al, 2000;Runft and Jaffe, 2000;Sato et al, 2000). For instance, inhibition of SFK signaling by injection of the SFK SH2 domain, or by various SFK inhibitors, prevented fertilization-associated activation of PLCc and [Ca 2+ ] i release in starfish and Xenopus eggs, and, consistent with these findings, activation of the egg SFK(s) was sufficient to induce PLCc activation and subsequent [Ca 2+ ] i release in these species Sato et al, 2000Sato et al, , 2003.…”
Section: Plccmentioning
confidence: 99%
“…In that paper, we showed data about chromatographic fractionation of membrane-associated proteins and in vitro protein kinase assay, by which we could detect an elevation of the activity of xSrc in response to fertilization. Our further studies demonstrated that pharmacological (e.g., use of inhibitors; Sato et al 1999Sato et al , 2000Sato et al , 2001 or molecular biological inhibition of xSrc (i.e., expression of kinase-negative mutant of xSrc; manuscript in preparation) impairs the ability of Xenopus eggs to undergo calcium reactions and egg activation in response to sperm and that Xenopus eggs can be activated in a Src-dependent manner by artifi cial egg activators that interacts with the egg surface (i.e., RGD peptide and cathepsin B; Sato et al 1999 ;Mahbub Hasan et al 2005 ) and by hydrogen peroxide that may directly activate xSrc (Sato et al 2001 ). These results suggest that xSrc acts between gamete interaction/fusion and an increase in intracellular calcium concentration at fertilization ( Fig.…”
Section: Characterization Of Src As a Mediator Of Gamete Interaction mentioning
confidence: 62%